Intracardiac Echocardiography to Guide Non-fluoroscopic Electrophysiology Procedures - Kautzner, Josef; Haskova, Jana; Lehar, Frantisek (Cardiac electrophysiology clinics, 2021)
Intracardiac echocardiography (ICE) is the most practical method for online imaging during electrophysiological procedures. It allows guiding of complex catheter ablation procedures together with electroanatomical mapping systems, either with minimal or with zero fluoroscopy exposure. Besides safe and reproducible transseptal puncture, ICE helps to assess location and contact of the tip of the ablation catheter relative to specific anatomical structures. Another option is visualization of the arrhythmogenic substrate in patients with ventricular arrhythmias. This article describes the clinical utility of ICE in non-fluoroscopic electrophysiology procedures more in detail.
Keywords: srdce; Fluoroscopy; Electrophysiologic Techniques, Cardiac; elektrofyziologické techniky kardiologické; lidé; katetrizační ablace; chirurgie s pomocí počítače; srdeční arytmie; Arrhythmias, Cardiac; Echocardiography; Heart; Humans; Catheter Ablation; fluoroskopie; Surgery, Computer-Assisted; echokardiografie